Isaac Newton and the Problem of Action at Distance - Henry, John (Estudios de Filosofía, 2007)
Action at a distance has more often than not been regarded as an unacceptable means of explanation in physics. Seeming to defy all attempts to assign proper causes to effects, action at a distance has generally been eschewed as occultist nonsense. The rejection of action at a distance was a major precept of the Aristotelianism which was so long dominant in European natural philosophy, and, it remains to this day a major assumption of our modern physics. There was, however, a period of interregnum; a period when actions at a distance were readily accepted by the majority of natural philosophers. The major influence on this radical new approach to the nature of physical causation was, of course, Isaac Newton. Newton’s universal principle of gravitation seemed to many to provide not only an undeniable example of a force of nature which could not be reduced to any kind of mechanical contact action between bodies, but also a model for other putative forces which might be supposed to account for chemical, biological and other physical phenomena. Throughout the eighteenth century, therefore, as a number of important historical studies have shown, natural philosophers sought to bring to fruition Newton’s wish, expressed in the Preface to the Principia, that all the phenomena of nature be explained in terms of attractive and repulsive forces operating at a distance between the minutest particles of bodies. So great is the modern prejudice against the legitimacy of actions at a distance, however, that a number of leading Newtonian scholars have insisted that Newton never really believed in actio in distans and was completely misunderstood by the succeeding generation. This paper reasserts that Newton did believe in action at a distance and refutes the arguments of recent Newtonian scholars that he did not.